Friction material, application of friction material, fan brake pad and preparation method of fan brake pad
By using friction materials prepared by aluminum powder and other materials, the problems of traditional wind turbine brake pads are solved, and the brake pads of wind turbines are lightweight, high wear resistance and low noise are achieved, and the brake pads of wind turbines are lightweight, high wear resistance and low noise are met, meeting the efficient and stable operation needs of wind turbines in complex environments.
Patent Information
- Application Number
- CN202411737133.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-02-28
AI Technical Summary
Traditional wind turbine brake pad materials have problems such as heavy weight, poor wear resistance, and high braking noise, which affects the overall performance and operating efficiency of wind turbines.
A friction material is used, including aluminum powder, aluminum fiber, iron fiber, copper fiber, copper powder, iron powder, aluminum ferroalloy powder, aluminum lithium alloy powder, graphite, molybdenum disulfide and aluminum oxide, to prepare fan brake pads. The material is prepared by cold press forming and sintering to form a combined structure of the steel back and the friction block.
It has achieved lightweight, high wear resistance, low noise and stable friction coefficient of wind turbine brake pads, meeting the efficient and stable operation needs of wind turbines in complex environments.
Smart Images

Figure CN119525484A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fan brake pads, and in particular to a friction material and a use thereof, a fan brake pad and a preparation method thereof. Background Art
[0002] Wind power generation refers to converting the kinetic energy of wind into electrical energy. Using wind power to generate electricity is very environmentally friendly and has huge wind energy reserves, so it is increasingly valued by countries around the world. China is rich in wind energy resources, with a wind energy reserve that can be developed and utilized of about 1 billion kW, of which about 253 million kW is on land (calculated based on data at a height of 10m above the ground), and about 750 million kW is offshore, totaling 1 billion kW. At the end of 2003, the national installed power capacity was about 567 million kW.
[0003] With the continuous development of wind power generation technology, wind turbines have higher and higher requirements for the braking system. Traditional brake pad materials often have problems such as heavy weight, poor wear resistance, and loud braking noise, which affect the overall performance and operating efficiency of wind turbines. Therefore, it is of great significance to develop a new type of brake pad material for wind turbines. Summary of the invention
[0004] In view of the above problems existing in the prior art, the present invention provides a friction material and its use, a wind turbine brake pad and its preparation method, so as to improve the overall performance and operation efficiency of the wind turbine.
[0005] To achieve the above-mentioned purpose and other related purposes, the first aspect of the present invention provides a friction material, which comprises the following components, measured by mass percentage of the friction material: 30% to 50% aluminum powder, 5% to 10% aluminum fiber, 1% to 6% iron fiber, 2% to 5% copper fiber, 5% to 10% copper powder, 3% to 15% iron powder, 5% to 8% aluminum-iron alloy powder, 5% to 10% aluminum-lithium alloy powder, 3% to 10% graphite, 0.3% to 3% molybdenum disulfide, and 1% to 5% aluminum oxide.
[0006] In one embodiment of the present invention, the addition amount of the aluminum powder is 32% to 50%, the addition amount of the aluminum fiber is 6% to 9.3%, the addition amount of the iron fiber is 2% to 5%, the addition amount of the copper fiber is 3% to 5%, the addition amount of the copper powder is 5% to 9%, and the addition amount of the iron powder is 5% to 15%.
[0007] In one embodiment of the present invention, the addition amount of the aluminum-lithium alloy powder is 5% to 9%, the addition amount of the graphite is 3% to 9%, the addition amount of the molybdenum disulfide is 0.5% to 3%, and the addition amount of the aluminum oxide is 1% to 4%.
[0008] A second aspect of the present invention provides a use of a friction material, characterized in that the friction material is used for a fan brake pad.
[0009] A third aspect of the present invention provides a fan brake pad, which includes a steel back and a friction block made of the above-mentioned friction material.
[0010] A fourth aspect of the present invention provides a method for preparing a fan brake pad, comprising the following steps:
[0011] Mixing of raw materials of friction materials: weigh the friction materials according to the proportion and place them in the mixer to mix evenly;
[0012] Cold pressing: putting the evenly mixed friction material into a mold for pressing to obtain a friction block blank;
[0013] Sintering: The friction block blank is bonded to the steel back and placed in a sintering furnace for sintering to obtain a fan brake pad.
[0014] In one embodiment of the present invention, the pressing pressure of the cold press forming is 450-850 Mp, and the pressing time is 30-60 s.
[0015] In one embodiment of the present invention, the sintering temperature of the sintering treatment is 600-850° C., the sintering pressure is 3-8 MPa, and the sintering time is 5-8 hours.
[0016] In one embodiment of the present invention, the sintering process is protected by reducing gas or a mixed gas of reducing gas and inert gas.
[0017] In one embodiment of the present invention, the sintering process uses a mixed gas of reducing gas and inert gas for protection, and the volume ratio of the reducing gas to the inert gas is 3:1 to 1:1.
[0018] The friction material of the present invention uses aluminum powder as a base material, and is added with high-strength aluminum fiber, iron fiber, and copper fiber as reinforcing materials. At the same time, aluminum-iron alloy powder and aluminum-lithium alloy powder are added to improve the reinforcing phase of the fan brake pad. The aluminum-iron alloy powder and aluminum-lithium alloy powder are eutectic with aluminum powder, iron powder, and copper powder at high temperature, which can not only improve the matrix strength, but also increase the friction coefficient of the fan brake pad; adding aluminum oxide as a wear-increasing material, using graphite and molybdenum disulfide as lubricating components, can protect the pair and stabilize the friction coefficient. The fan brake pad prepared by the friction material of the present application is light in weight, has the characteristics of excellent braking performance, high wear resistance, low noise, light weight, stable friction coefficient, etc., and can meet the needs of efficient and stable operation of wind turbines in complex environments. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only some embodiments of the present invention. For ordinary technicians in this field, other embodiments can be obtained based on these drawings without paying creative work.
[0020] Figure 1 The present invention is a flow chart of the preparation of a fan brake pad in one embodiment. DETAILED DESCRIPTION
[0021] The following is an explanation of the embodiments of the present invention by specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the features in the following embodiments and the embodiments can be combined with each other without conflict. It should also be understood that the terms used in the embodiments of the present invention are intended to describe specific embodiments, rather than to limit the scope of protection of the present invention. The test methods for which specific conditions are not specified in the following examples are usually carried out under conventional conditions or according to the conditions recommended by the manufacturers.
[0022] When numerical ranges are given in the embodiments, it should be understood that unless otherwise specified in the present invention, both endpoints of each numerical range and any value between the two endpoints can be selected. Unless otherwise defined, all technical and scientific terms used in the present invention are familiar to those skilled in the art and the description of the present invention, and any method, device and material of the prior art similar or equivalent to the method, device and material in the embodiments of the present invention can also be used to implement the present invention.
[0023] It should be noted that the terms such as "upper", "lower", "left", "right", "middle" and "one" etc. used in this specification are only for the convenience of description and are not intended to limit the scope of implementation of the present invention. Changes or adjustments to their relative relationships, without substantially changing the technical content, should also be regarded as the scope of implementation of the present invention.
[0024] The invention provides a friction material. The friction material comprises the following components, measured by mass percentage of the friction material: 30% to 50% of aluminum powder, 5% to 10% of aluminum fiber, 1% to 6% of iron fiber, 2% to 5% of copper fiber, 5% to 10% of copper powder, 3% to 15% of iron powder, 5% to 8% of aluminum-iron alloy powder, 5% to 10% of aluminum-lithium alloy powder, 3% to 10% of graphite, 0.3% to 3% of molybdenum disulfide and 1% to 5% of aluminum oxide.
[0025] In one embodiment, the addition amount of aluminum powder is 32% to 50%, the addition amount of aluminum fiber is 6% to 9.3%, the addition amount of iron fiber is 2% to 5%, the addition amount of copper fiber is 3% to 5%, the addition amount of copper powder is 5% to 9%, and the addition amount of iron powder is 5% to 15%.
[0026] In one embodiment, the addition amount of aluminum-iron alloy powder is 5% to 8%, the addition amount of aluminum-lithium alloy powder is 5% to 9%, the addition amount of graphite is 3% to 9%, the addition amount of molybdenum disulfide is 0.5% to 3%, and the addition amount of aluminum oxide is 1% to 4%.
[0027] The present invention provides a use of a friction material. The friction material of the present invention uses aluminum powder as a base material, and is added with high-strength aluminum fiber, iron fiber, and copper fiber as reinforcing materials. At the same time, aluminum-iron alloy powder and aluminum-lithium alloy powder are added to improve the reinforcing phase of a fan brake pad. The aluminum-iron alloy powder and the aluminum-lithium alloy powder are eutectic with the aluminum powder, iron powder, and copper powder at high temperature, which can not only improve the base strength, but also increase the friction coefficient of the fan brake pad. Aluminum oxide is added as a wear-increasing material, and graphite and molybdenum disulfide are used as lubricating components to protect the pair and stabilize the friction coefficient. The fan brake pad prepared by using the friction material of the present application is light in weight, has the characteristics of excellent braking performance, high wear resistance, low noise, light weight, stable friction coefficient, etc., and can meet the requirements of efficient and stable operation of wind turbines in complex environments. Therefore, the friction material of the present invention is suitable for fan brake pads.
[0028] The invention provides a fan brake pad, comprising a steel back and a friction block made of the above friction material.
[0029] See also Figure 1 The present invention also provides a method for preparing a fan brake pad, comprising the following steps:
[0030] S1. Mixing of raw materials of friction materials: weigh the friction materials according to the proportion and place them in a mixer for uniform mixing;
[0031] S2, cold pressing: putting the uniformly mixed friction material into a mold for pressing and forming to obtain a friction block blank;
[0032] S3, sintering: putting the friction block blank and the steel back into a sintering furnace for sintering to obtain a fan brake pad.
[0033] In step S1, the friction material includes the following components in terms of mass percentage of the friction material raw material components: 30% to 50% aluminum powder, 5% to 10% aluminum fiber, 1% to 6% iron fiber, 2% to 5% copper fiber, 5% to 10% copper powder, 3% to 15% iron powder, 5% to 8% aluminum-iron alloy powder, 5% to 10% aluminum-lithium alloy powder, 3% to 10% graphite, 0.3% to 3% molybdenum disulfide, and 1% to 5% aluminum oxide. In one embodiment, the addition amount of aluminum powder is 32% to 50%, the addition amount of aluminum fiber is 6% to 9.3%, the addition amount of iron fiber is 2% to 5%, the addition amount of copper fiber is 3% to 5%, the addition amount of copper powder is 5% to 9%, and the addition amount of iron powder is 5% to 15%. In another embodiment, the addition amount of aluminum-iron alloy powder is 5% to 8%, the addition amount of aluminum-lithium alloy powder is 5% to 9%, the addition amount of graphite is 3% to 9%, the addition amount of molybdenum disulfide is 0.5% to 3%, and the addition amount of aluminum oxide is 1% to 4%.
[0034] In step S2, the pressing pressure of the cold press forming is 450-850 MPa, such as any value in the range of 450-850 MPa, such as 450 MPa, 500 MPa, 600 MPa, 700 MPa, 800 MPa or 850 MPa; the pressing time is 30-60 s, such as any value in the range of 30 s, 40 s, 50 s or 60 s. In the present invention, the cold press forming is performed at room temperature.
[0035] In step S3, the sintering temperature of the sintering treatment is 600-850°C, for example, any value of 600°C, 650°C, 700°C, 800°C or 850°C, and the sintering pressure is 3-8MPa, for example, any value of 3MPa, 5MPa, 7MPa or 8MPa, and the sintering time is 5-8h, for example, 5h, 6h, 7h or 8h. In one embodiment, the sintering treatment uses a reducing gas or a mixed gas of a reducing gas and an inert gas for protection. Exemplarily, a reducing gas can be used for protection, for example, pure hydrogen can be used for protection; a mixed gas of a reducing gas and an inert gas can also be used for protection, for example, a mixed gas of hydrogen and nitrogen. In this embodiment, a mixed gas of hydrogen and nitrogen is used for protection, and exemplary, the volume ratio of hydrogen to nitrogen is 3:1-1:1, for example, any value of 3:1-1:1, such as 3:1, 2:1 or 1:1. In other embodiments, other reducing gases and inert gases commonly used in the art may also be used to protect the sintering process. In some embodiments, positioning pieces are provided on the friction block blank and the steel back to ensure that the relative positions of the friction block blank and the steel back are accurate.
[0036] The technical scheme of the present invention is described in detail below through several specific examples. Unless otherwise specified, the raw materials and reagents used in the following examples are all commercially available products, or can be prepared by conventional methods in the art, and the instruments used in the examples are all commercially available.
[0037] Example 1
[0038] The preparation method of the fan brake pad in this embodiment is as follows: (1) Mixing the raw materials of the friction material: the friction material is weighed according to the ratio of 32% aluminum powder, 8% aluminum fiber, 5% iron fiber, 5% copper fiber, 10% copper powder, 15% iron powder, 8% aluminum-iron alloy powder, 5% aluminum-lithium alloy powder, 5% graphite, 3% molybdenum disulfide, and 4% aluminum oxide, and the weighed friction material is placed in a mixer and mixed evenly; (2) Cold pressing: the evenly mixed friction material is placed in a mold of a CNC press and pressed into shape at a pressing pressure of 500 MPa and a pressing time of 50 seconds to obtain a friction block blank; (3) Friction block sintering: the friction block blank is bonded to the steel back and placed in a sintering furnace, and sintered under the protection of hydrogen and nitrogen (3:1) at a sintering pressure of 5 MPa, a sintering temperature of 650°C, and a sintering time of 6 hours to obtain a fan brake pad.
[0039] Example 2
[0040] The preparation method of the fan brake pad in this embodiment is as follows: (1) Mixing the raw materials of the friction material: the friction material is weighed according to the ratio of 40% aluminum powder, 8% aluminum fiber, 5% iron fiber, 3% copper fiber, 8% copper powder, 14% iron powder, 6% aluminum-iron alloy powder, 5% aluminum-lithium alloy powder, 5% graphite, 2% molybdenum disulfide, and 4% aluminum oxide, and the weighed friction material is placed in a mixer and mixed evenly; (2) Cold pressing: the evenly mixed friction material is placed in a mold of a CNC press and pressed into shape at a pressing pressure of 500 MPa and a pressing time of 50 seconds to obtain a friction block blank; (3) Sintering: the friction block blank is laminated with a steel back and placed in a sintering furnace, and sintered under the protection of hydrogen and nitrogen (2:1) at a sintering pressure of 5 MPa, a sintering temperature of 650°C, and a sintering time of 6 hours to obtain a fan brake pad.
[0041] Example 3
[0042] The preparation method of the fan brake pad in this embodiment is as follows: (1) Mixing the raw materials of the friction material: weighing the proportions of 50% aluminum powder, 5% aluminum fiber, 5% iron fiber, 3% copper fiber, 5% copper powder, 10% iron powder, 6% aluminum-iron alloy powder, 5% aluminum-lithium alloy powder, 5% graphite, 2% molybdenum disulfide, and 4% aluminum oxide, and placing the weighed friction materials in a mixer for uniform mixing; (2) Cold pressing: placing the uniformly mixed friction materials into a mold of a CNC press for pressing and molding at a pressing pressure of 500 MPa and a pressing time of 50 s to obtain a friction block blank; (3) Sintering: placing the friction block blank and the steel back in a sintering furnace, and sintering treatment is performed under the protection of hydrogen and nitrogen (3:1) at a sintering pressure of 5 MPa, a sintering temperature of 650°C, and a sintering time of 6 h to obtain a fan brake pad.
[0043] Example 4
[0044] The preparation method of the fan brake pad in this embodiment is as follows: (1) Mixing the raw materials of the friction material: the friction material is weighed according to the ratio of 40% aluminum powder, 9.3% aluminum fiber, 2% iron fiber, 4% copper fiber, 9% copper powder, 11% iron powder, 5% aluminum-iron alloy powder, 10% aluminum-lithium alloy powder, 4% graphite, 2.7% molybdenum disulfide, and 3% aluminum oxide, based on the mass percentage of the friction material, and the weighed friction material is placed in a mixer and mixed evenly; (2) Cold pressing: the evenly mixed friction material is placed in a mold of a CNC press and pressed into shape at a pressing pressure of 450 MPa and a pressing time of 60 seconds to obtain a friction block blank; (3) Sintering: the friction block blank is bonded to the steel back and placed in a sintering furnace, and sintered under the protection of hydrogen and nitrogen (1:1) at a sintering pressure of 8 MPa, a sintering temperature of 600°C, and a sintering time of 7 hours to obtain a fan brake pad.
[0045] Example 5
[0046] The preparation method of the fan brake pad in this embodiment is as follows: (1) Mixing the raw materials of the friction material: weigh the friction material according to the ratio of 47.5% aluminum powder, 10% aluminum fiber, 6% iron fiber, 2% copper fiber, 5% copper powder, 3% iron powder, 7% aluminum-iron alloy powder, 9% aluminum-lithium alloy powder, 9% graphite, 0.5% molybdenum disulfide, and 1% aluminum oxide, based on the mass percentage of the friction material, and place the weighed friction material in a mixer for uniform mixing; (2) Cold pressing: put the uniformly mixed friction material into the mold of a CNC press and press it into shape at a pressing pressure of 700 MPa and a pressing time of 40 seconds to obtain a friction block blank; (3) Sintering: put the friction block blank and the steel back into a sintering furnace for sintering under the protection of hydrogen at a sintering pressure of 6 MPa, a sintering temperature of 800°C, and a sintering time of 5 hours to obtain a fan brake pad.
[0047] Example 6
[0048] The preparation method of the fan brake pad in this embodiment is as follows: (1) Mixing the raw materials of the friction material: the friction material is weighed according to the ratio of 30% aluminum powder, 6% aluminum fiber, 6% iron fiber, 5% copper fiber, 10% copper powder, 15% iron powder, 6% aluminum-iron alloy powder, 6.7% aluminum-lithium alloy powder, 10% graphite, 0.3% molybdenum disulfide, and 5% aluminum oxide, and the weighed friction material is placed in a mixer and mixed evenly; (2) Cold pressing: the evenly mixed friction material is placed in a mold of a CNC press and pressed into shape at a pressing pressure of 850 MPa and a pressing time of 30 seconds to obtain a friction block blank; (3) Sintering: the friction block blank is laminated with a steel back and placed in a sintering furnace, and sintered under the protection of hydrogen and nitrogen (3:1) at a sintering pressure of 4 MPa, a sintering temperature of 850°C, and a sintering time of 6 hours to obtain a fan brake pad.
[0049] Example 7
[0050] The preparation method of the fan brake pad in this embodiment is as follows: (1) Mixing the raw materials of the friction material: the friction material is weighed according to the ratio of 48% aluminum powder, 10% aluminum fiber, 1% iron fiber, 5% copper fiber, 10% copper powder, 5% iron powder, 6% aluminum-iron alloy powder, 8% aluminum-lithium alloy powder, 3% graphite, 2% molybdenum disulfide, and 2% aluminum oxide, and the weighed friction material is placed in a mixer and mixed evenly; (2) Cold pressing: the evenly mixed friction material is placed in a mold of a CNC press and pressed into shape at a pressing pressure of 600 MPa and a pressing time of 45 seconds to obtain a friction block blank; (3) Sintering: the friction block blank is laminated with a steel back and placed in a sintering furnace, and sintered under the protection of hydrogen and nitrogen (3:1) at a sintering pressure of 3 MPa, a sintering temperature of 700°C, and a sintering time of 8 hours to obtain a fan brake pad.
[0051] The aluminum powder, copper powder, iron powder, aluminum-iron alloy powder, aluminum-lithium alloy powder, graphite, molybdenum disulfide, and aluminum oxide in Examples 1 to 7 are all selected from conventional raw materials in the field and can be obtained through general commercial channels; the aluminum fibers, iron fibers, and copper fibers can adopt the aluminum fiber, iron fiber, and copper fiber specifications well known to those skilled in the art, and can be obtained through general commercial channels, and the lengths of the aluminum fibers, iron fibers, and copper fibers are 0.1 to 1.0 mm.
[0052] According to the JB / T 10426.2 standard test, the performance of the fan brake pads prepared in Examples 1 to 7 was tested, and the test results are shown in Table 1:
[0053]
[0054] As can be seen from Table 1, the physical and mechanical properties of the fan brake pads of this application are in accordance with the relevant provisions of the JB / T10426.2 standard, and the density is relatively low, which meets the use requirements of high-load wind turbine generator sets. At the same time, the friction coefficient of the fan brake pad is as high as 0.34, and the friction coefficient is highly stable. Under the same braking pressure, the volatility is within the range of 10%, and the braking safety is high; the wet friction coefficient of the fan brake pad can reach 0.3, and under the same braking pressure, the volatility is within the range of 10%, which can ensure safe braking in rainy weather, and meet the efficient and stable operation requirements of wind turbines in complex environments. At the same time, the noise detection results of the brake pads show that the probability of noise greater than or equal to 80db is about 0.01%, indicating that the brake pads of this application have low noise when in use; at the same time, the wear rate of the brake pads is low, indicating that it has good wear resistance.
[0055] The friction material of the present invention uses aluminum powder as a base material, and adds high-strength aluminum fiber, iron fiber, and copper fiber as reinforcing materials. At the same time, aluminum-iron alloy powder and aluminum-lithium alloy powder are added to improve the reinforcing phase of the fan brake pad. The aluminum-iron alloy powder and aluminum-lithium alloy powder are eutectic with aluminum powder, iron powder, and copper powder at high temperature, which can not only improve the matrix strength, but also increase the friction coefficient of the fan brake pad; adding aluminum oxide as a wear-increasing material, using graphite and molybdenum disulfide as lubricating components, can protect the pair and stabilize the friction coefficient. The fan brake pad prepared by the friction material of the present application is light in weight, has excellent braking performance, high wear resistance, low noise, light weight, and stable friction coefficient, and can meet the requirements of efficient and stable operation of wind turbines in complex environments. In addition, the friction material and the fan brake pad of the present invention do not contain elements such as asbestos, lead, cadmium, hexavalent chromium, etc., and have good environmental performance. Therefore, the present invention effectively overcomes some practical problems in the prior art and has high utilization value and use significance.
[0056] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A friction material, characterized in that: Measured in percentage by mass of the friction material, the friction material includes the following components: 30% to 50% aluminum powder, 5% to 10% aluminum fiber, 1% to 6% iron fiber, 2% to 5% copper fiber, 5% to 10% copper powder, 3% to 15% iron powder, 5% to 8% aluminum-iron alloy powder, 5% to 10% aluminum-lithium alloy powder, 3% to 10% graphite, 0.3% to 3% molybdenum disulfide, and 1% to 5% aluminum oxide.
2. The friction material according to claim 1, characterized in that: The addition amount of the aluminum powder is 32% to 50%, the addition amount of the aluminum fiber is 6% to 9.3%, the addition amount of the iron fiber is 2% to 5%, the addition amount of the copper fiber is 3% to 5%, the addition amount of the copper powder is 5% to 9%, and the addition amount of the iron powder is 5% to 15%.
3. The friction material according to claim 1, characterized in that: The addition amount of the aluminum-lithium alloy powder is 5% to 9%, the addition amount of the graphite is 3% to 9%, the addition amount of the molybdenum disulfide is 0.5% to 3%, and the addition amount of the aluminum oxide is 1% to 4%.
4. Use of the friction material according to any one of claims 1 to 3, characterized in that: The friction material is used for fan brake pads.
5. A fan brake pad, characterized in that: The invention comprises a steel back and a friction block made of the friction material according to any one of claims 1 to 3.
6. A method for preparing a fan brake pad according to claim 5, characterized in that: The following steps are involved: Mixing of raw materials of friction materials: weigh the friction materials according to the proportion and place them in the mixer to mix evenly; Cold pressing: putting the evenly mixed friction material into a mold for pressing to obtain a friction block blank; Sintering: The friction block blank is bonded to the steel back and placed in a sintering furnace for sintering to obtain a fan brake pad.
7. The preparation method according to claim 6, characterized in that: The pressing pressure of the cold pressing molding is 450-850Mp, and the pressing time is 30-60s.
8. The preparation method according to claim 6, characterized in that: The sintering temperature of the sintering treatment is 600-850° C., the sintering pressure is 3-8 MPa, and the sintering time is 5-8 hours.
9. The preparation method according to claim 6, characterized in that: The sintering process uses reducing gas or a mixed gas of reducing gas and inert gas for protection.
10. The preparation method according to claim 9, characterized in that: The sintering process uses a mixed gas of reducing gas and inert gas for protection, and the volume ratio of the reducing gas to the inert gas is 3:1 to 1:1.